Functional and smart materials - Davim, J. Paulo; Prakash, Chander; Singh, Sunpreet , 1989- (Manufacturing design and technology, 2021)
"This book presents a comprehensive and broad-spectrum picture of the state-of-the-art research, development, and commercial prospective of various discoveries conducted in the real-world of functional and smart materials. The book presents the various synthesis and fabrication route of functional and smart materials for universal applications such as material science, mechanical engineering, manufacturing, metrology, nanotechnology, physics, chemical, biology, chemistry, civil engineering, and food science. The content of this book opens the various scientific horizons which are proved to be of utmost beneficial for uplifting the standards of the day-to-day practices in the biomedical domain. Noticeably, myriads of innovations in the materials science and engineering are transforming our day-to-day life in an extraordinary manner. The book has captured emerging areas of materials science and advanced manufacturing engineering and presents the recent trends in research for young researchers, field engineers, and academic professionals"-- Provided by publisher